2013
DOI: 10.1161/circimaging.113.000488
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Computed Tomographic and Magnetic Resonance Imaging in a Murine Model of Progressive Atherosclerosis Using 64 Cu-Labeled Glycoprotein VI-Fc

Abstract: R upture of vulnerable atherosclerotic plaque is a major cause of coronary thrombosis and subsequent myocardial infarction. Fibrillar collagen is the most abundant extracellular matrix protein in artery walls. It acts as a strong platelet activator and initiates platelet-dependent thrombus formation.1,2 Platelet glycoprotein VI (GPVI) binds to exposed subendothelial collagen as a result of vascular injury or atherosclerosis. 2 We recently performed optical imaging experiments in a mouse model of vascular injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Further, there have been no reports of aberrant platelet activation, loss of GPVI on circulating platelets, or thrombocytopenia associated with the use of this reagent in animal models. By the addition of an appropriate molecular tag to GPVI-Fc, it is possible that this reagent may also be developed as a bioimaging tool as it selectively binds to presumably prothrombotic regions of a vascular bed that is enriched for collagen 16,98,101…”
Section: Targeting Gpvi Therapeuticallymentioning
confidence: 99%
“…Further, there have been no reports of aberrant platelet activation, loss of GPVI on circulating platelets, or thrombocytopenia associated with the use of this reagent in animal models. By the addition of an appropriate molecular tag to GPVI-Fc, it is possible that this reagent may also be developed as a bioimaging tool as it selectively binds to presumably prothrombotic regions of a vascular bed that is enriched for collagen 16,98,101…”
Section: Targeting Gpvi Therapeuticallymentioning
confidence: 99%
“…The soluble dimeric fusion protein GPVI-Fc, initially designed as an antithrombotic, was shown to exhibit a high affinity towards collagen in various studies 37. Radioactive or fluorescence labeling enabled the visualization of vascular injury in the carotid arteries and the aortic arch of mice, notably with optical imaging 38 and PET 21, 39. It was later shown that GPVI binds not only to collagen fiber but also to most ECM proteins 19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…While initially developed for use in atherosclerotic patients as an antithrombotic agent devoid of influence on general hemostasis in humans 17, GPVI-Fc was shown to have a high affinity to multiple components of the ECM, such as collagen 18, fibronectin19 and notably fibrinogen/fibrin 20, with K D values of around 2 µg/mL 19. We, thus, developed an efficient 64 Cu labeling method to initially yield [ 64 Cu]Cu-NOTA-GPVI-Fc ( 64 Cu-GPVI-Fc, Figure 1B ) for atherosclerosis 21, and show herein its potential as a fibrosis-driven PET imaging agent in selected inflammatory disease models: a trinitrochlorobenzene (TNCB)-induced cutaneous delayed-type hypersensitivity (DTHR), giving access to both acute and chronic inflammation states 22; anti-glucose-6-phosphate isomerase (GPI)-serum induced rheumatoid arthritis (RA), a chronic inflammation model presenting extensive permeation of the synovia with a progressive appearance of a fibrous cap; lipopolysaccharide (LPS)-induced subchronic lung inflammation, devoid of fibrosis; and experimental autoimmune encephalomyelitis (EAE), a progressive spinal cord and brain inflammation model presenting light fibrosis around capillary vessels. All of these models are imaged multimodally and noninvasively in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant targets of plaque vulnerability, investigated through nuclear medicine imaging in the ApoE −/− murine model, include other biomarkers of inflammation such as the following: P-selectin [ 247 , 248 ]; α v β 3 receptor with an RGD-galacto peptide [ 249 ] or the novel integrin ligand flotegatide [ 250 ], both labeled with fluorine-18; phosphatidylserine using 99 mTc-annexin V [ 197 ] or 99 mTc-AnxF568 and 124 I-Hypericin [ 251 ] for apoptosis imaging; and extracellular matrix proteins such as GPVI with a 64 Cu-labeled GPVI fragment crystallized [ 252 ] or fibronectin using a specific 99 mTc-antibody [ 253 ]. Finally, in an attempt to improve the detection of vulnerable lesions, contrast agents for CT imaging of macrophage-rich atherosclerotic plaques have been developed and tested in the major mouse models of atherosclerosis, for example liposomal-iodine [ 254 ] or PEGylated gold nanoparticles [ 255 ] in ApoE −/− mice and, more recently, gold particles of 15 nm with a polyethylene glycol coating called Aurovist in the ApoE −/− C1039G +/− model [ 43 ].…”
Section: Murine Models Of Atherosclerosis and Molecular Imaging Tamentioning
confidence: 99%